The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/min9030195
|View full text |Cite
|
Sign up to set email alerts
|

Magma Mixing Genesis of the Mafic Enclaves in the Qingshanbao Complex of Longshou Mountain, China: Evidence from Petrology, Geochemistry, and Zircon Chronology

Abstract: The Qingshanbao complex, part of the uranium metallogenic belt of the Longshou-Qilian mountains, is located in the center of the Longshou Mountain next to the Jiling complex that hosts a number of U deposits. However, little research has been conducted in this area. In order to investigate the origin and formation of mafic enclaves observed in the Qingshanbao body and the implications for magmatic-tectonic dynamics, we systematically studied the mineralogy, petrography, and geochemistry of these enclaves. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The zircon grains from the K‐feldspar granite ( n = 14) have Th and U average content of 315 and 378 ppm, respectively, and yielded concordia age of 442 ± 4.2 Ma (MSWD = 1.4; Figure 4b). The zircons from the granodiorite ( n = 16) have higher concentrations of Th (avg = 551 ppm) and U (avg = 630 ppm) than the ones from the K‐feldspar granite and diorite and yielded a concordant age of 433 ± 4.2 Ma (MSWD = 1.8; Figure 4c; Liu et al, 2019a). The diorite zircon grains have average concentrations of U and Th of 369 and 249 ppm, respectively, and yielded a concordia age of 439 ± 4.7 Ma (MSWD = 1.1; Figure 4d).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The zircon grains from the K‐feldspar granite ( n = 14) have Th and U average content of 315 and 378 ppm, respectively, and yielded concordia age of 442 ± 4.2 Ma (MSWD = 1.4; Figure 4b). The zircons from the granodiorite ( n = 16) have higher concentrations of Th (avg = 551 ppm) and U (avg = 630 ppm) than the ones from the K‐feldspar granite and diorite and yielded a concordant age of 433 ± 4.2 Ma (MSWD = 1.8; Figure 4c; Liu et al, 2019a). The diorite zircon grains have average concentrations of U and Th of 369 and 249 ppm, respectively, and yielded a concordia age of 439 ± 4.7 Ma (MSWD = 1.1; Figure 4d).…”
Section: Resultsmentioning
confidence: 97%
“…(b and d) Concordia diagram for studied samples. Data for the granodiorite (QSB‐15) are from Liu et al (2019a)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The limpen original lithospheric rocks were taken away by asthenospheric mantle, resulting in the thinning of the lithosphere, simultaneously the frontal side of the subduction slab began to roll back [28], leading of an extensional environment. There are few records of the metamorphic core complexes or the extensional deformation in Xingcheng-Xudapu area during the Middle Jurassic [39], while voluminous Late Jurassic metamorphic core complexes, as well as extensional sedimentary basins, spread widely in western Liaoning [17,47,[67][68][69][70][71], which indicate the extensional structures [34,35,72]. For example, Xu et al [73] found the Late Jurassic gneissic granite in the eastern part of the NCC, in which the interstitial materials developed directionally, and pointed out that the rocks were formed in the apotectonic and extensional setting.…”
Section: Magmatic Activitives and Tectonic Evolution Of The Eastern Smentioning
confidence: 99%